Agroecological or conventional farming? Assessing the socioeconomic and environmental impacts of two agricultural systems in the agroforestry parklands of Burkina Faso - Aïcha Tapsoba; Josias Sanou; Hugues Roméo Bazié; Madelene Ostwald (Cogent Social Sciences)
Enhancing food production is a requirement for food security, particularly in a developing context. Innovation and techniques to lower input cost is one aspect that is needed to make the systems more resilient. Here we do a comparative costs and benefits analysis between agroecological and conventional farming practices in agroforestry parklands in two communes in Burkina Faso. Social and environmental concerns are included to highlight the requirements of the local context. A structured surveys and trials of maize and cowpea crops were carried out over two cropping seasons in the two agriculture practices. Result showed that agroecological practices are slightly costlier in terms of labor capital. However, in terms of inputs, input costs for both crops are higher in conventional farming (380 ± 2 US $ and 115 ± 4 US $) than in agroecological farming (285 ± 15 US $ and 56 ± 1 US $) for maize and cowpea crops, respectively. For cowpea production, the cost-benefit ratio was higher in agroecology than in conventional farming (2.37 ± 0.07 and 2.06 ± 0.05, respectively). In contrast, maize cultivation with conventional farming favored over agroecological farming (1.18 ± 0.02 and 0.99 ± 0.03 respectively). Agroecological practices should be promote and integrate into local agriculture policies for rural development, human and animal health and a sustainable production on agroforestry parklands.